Novel mutations in the ferritin-L iron-responsive element that only mildly impair IRP binding cause hereditary hyperferritinaemia cataract syndrome - Luscieti, Sara; Tolle, Gabriele; Aranda, Jessica; Campos, Carmen Benet; Risse, Frank; Morán, Érica; Muckenthaler, Martina; Sánchez, Mayka (Orphanet journal of rare diseases, 2013)
Hereditary Hyperferritinaemia Cataract Syndrome (HHCS) is a rare autosomal dominant disease characterized by increased serum ferritin levels and early onset of bilateral cataract. The disease is caused by mutations in the Iron-Responsive Element (IRE) located in the 5′ untranslated region of L-Ferritin (FTL) mRNA, which post-transcriptionally regulates ferritin expression.